Subcritical water extraction on phenolic, flavonoid and antioxidant activity from orthosiphon stamineus leaves: experimental and optimization - Sarah Aisyah Khurun Hizar; Nicky Rahmana Putra; Rovina Kobun; Siti Faridah Mohd Amin; Jumardi Roslan; Macdalyna Esther Ronie; Muhammad Abbas Ahmad Zaini; Hasmadi Mamat; Ahmad Hazim Abdul Aziz (Kuwait University, 2024)
Orthosiphon stamineus is rich in phenolic and flavonoid compounds, contributing to its antioxidant properties. This study focuses optimizes the extraction of bioactive compounds from Orthosiphon stamineus leaves using subcritical water (SCW) extraction. Response surface methodology was employed, with temperature (120–180 °C), flow rate (2–8 mL min−1), and extraction time (5–15 min) as independent variables. Dependent variables included extract yield, total phenolic compounds (TPC), total flavonoid compounds (TFC), and antioxidant activity (AA). Optimal conditions were found at 148 °C, 5.1 mL min−1, and 10.5 min, resulting in a maximum yield of 317.6 mg g−1, TPC of 12.71 mg 100 g−1, TFC of 74.09 mg 100 g−1, and AA of 87.48 %. The research highlights the significant influence of temperature as the most crucial parameter, followed by flow rate and extraction time, in achieving the highest yield and bioactive compound content. This investigation holds potential implications for the food processing industry, showcasing the relevance of optimizing extraction conditions to enhance the nutritional and functional properties of natural ingredients like Orthosiphon stamineus in food products.